TRANSFORMASI PERAN HUMAS PENDIDIKAN TINGGI: DARI FUNGSI ADMINISTRATIF MENUJU KEMITRAAN STRATEGIS DALAM MEMBANGUN REPUTASI INSTITUSI - Rofiq Setiawan; Rustam Ibrahim (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the transformation of public relations roles in higher education institutions from administrative functions toward strategic partnerships in building institutional reputation. The rapid changes in the higher education environment in the digital era require public relations not only to function as information disseminators and administrative executors, but also as strategic actors capable of building institutional image, public trust, and collaborative relationships with various stakeholders. This research employs a qualitative approach using the library research method through the analysis of scientific literature, academic journals, and relevant documents related to higher education public relations management. The findings indicate that the transformation of public relations in higher education is characterized by the strengthening of strategic communication functions, digital media management, institutional branding development, crisis management, and partnership building with communities, industries, and mass media. Modern public relations plays a strategic role as a bridge between institutions and both internal and external publics in creating a positive and sustainable reputation. Furthermore, the success of this transformation is influenced by the competence of human resources, leadership support, and adaptability to the development of information technology. This study confirms that public relations in higher education holds an essential position in enhancing institutional competitiveness and reputation amid global educational competition.